The sorcerer's apprentice: Liberalism, ideology, and religion in world politics. (June 2019) - Jahn, Beate
Despite repeated announcements of the end of ideology and the demise of religion during the twentieth century, both play a crucial role in world politics today. This disjuncture between theoretical expectations and historical developments has its roots in conventional conceptions of ideology. While the latter grasp the representative nature of ideology as an expression of historical forces and political interests, they miss its constitutive role for modern politics. Based on an analysis of its historical origins and political implications, this article develops a new conception of ideology which accounts for the resilience and historical dynamics of ideological struggle. Like the sorcerer's apprentice, I show, liberalism has called ideology into being but lost control of its own creation.